Candidate Gene Analysis Reveals That the Fruit Color Locus C1 Corresponds to PRR2 in Pepper (Capsicum frutescens) - Jeong, Hyo-Bong; Jang, So-Jeong; Kang, Min-Young; Kim, Suna; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2020)
The diverse fruit colors of peppers (Capsicum spp.) are due to variations in carotenoid composition and content. Mature fruit color in peppers is regulated by three independent loci, C1, C2, and Y. C2 and Y encode phytoene synthase (PSY1) and capsanthin-capsorubin synthase (CCS), respectively; however, the identity of the C1 gene has been unknown. With the aim of identifying C1, we analyzed two pepper accessions with different fruit colors: Capsicum frutescens AC08-045 and AC08-201, whose fruits are light yellow and white, respectively. Ultra-performance liquid chromatography showed that the total carotenoid content was six times higher in AC08-045 than in AC08-201 fruits, while the composition and the proportions of different carotenoids were similar, suggesting that a genetic factor in AC08-201 may down-regulate overall carotenoid biosynthesis. Analyses of candidate genes related to carotenoid biosynthetic and plastid abundance revealed that both accessions carry nonfunctional alleles of CCS, golden2-like transcription factor (GLK2), and PSY1. However, a nonsense mutation (C2571T) in PRR2, a homologue of Arabidopsis pseudo response regulator2-like (APRR2), was present in only AC08-201. In a population derived from a cross between AC08-045 and AC08-201, an SNP marker based on the nonsense mutation co-segregated fully with fruit color, implying that the mutation in PRR2 may cause the white color of AC08-201 fruits. Transmission electron microscopy (TEM) of AC08-201 fruit pericarp also showed less developed granum structure in chloroplast and smaller plastoglobule in chromoplast compared to those of AC08-045. Virus-induced gene silencing (VIGS) of PRR2 significantly reduced carotenoid accumulation in Capsicum annuum ‘Micropep Yellow’, which carries nonfunctional mutations in both PSY1 and CCS. Furthermore, sequence analysis of PSY1, CCS, and PRR2 in other white pepper accessions of C. annuum and Capsicum chinense showed that they commonly have nonfunctional alleles in PSY1, CCS, and PRR2. Thus, our data demonstrate that the fruit color locus C1 in Capsicum spp. corresponds to the gene PRR2.